2007
DOI: 10.1007/s10462-008-9090-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and improvement of quality of service in wireless networks using fuzzy and hybrid genetic-fuzzy approaches

Abstract: Fuzzy and hybrid genetic-fuzzy approaches were used to assess and improve quality of service (QoS) in simulated wireless networks. Three real-time audio and video applications were transmitted over the networks. The QoS provided by the networks for each application was quantitatively assessed using a fuzzy inference system (FIS). Two methods to improve the networks' QoS were developed. One method was based on a FIS mechanism and the other used a hybrid genetic-fuzzy system. Both methods determined an optimised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Mohammad et al [12] applied Fuzzy logic technique to improve the quality of service in the audio and video applications. Parameters like delay, jitter, throughput, packet loss and both are combined into a single value that is the input of fuzzy inference system.…”
Section: K Santhi K Thinakaranmentioning
confidence: 99%
“…Mohammad et al [12] applied Fuzzy logic technique to improve the quality of service in the audio and video applications. Parameters like delay, jitter, throughput, packet loss and both are combined into a single value that is the input of fuzzy inference system.…”
Section: K Santhi K Thinakaranmentioning
confidence: 99%
“…The Wireshark network monitoring captured RTP packets (installed on two of the PCs) that were sorted using their sequence numbers to determine end-to-end delay, jitter, and percentage packet loss ratio as outlined below [27][28][29].…”
Section: Network Traffic Parametersmentioning
confidence: 99%
“…An assessment and QoS improvement in wireless networks using hybrid genetic-fuzzy approaches was investigated by Saraireh, et al , [15] . This indicated that devised methods effectively assessed and significantly improved QoS in wireless networks.…”
Section: Literatue Reviewmentioning
confidence: 99%